2021
DOI: 10.1177/13623613211044345
|View full text |Cite
|
Sign up to set email alerts
|

The influence of race on parental beliefs and concerns during an autism diagnosis: A mixed-method analysis

Abstract: The purpose of this mixed-method study was to examine racial differences in parental beliefs and concern about autism spectrum disorder (ASD) versus clinical judgment. The sample included 489 children with ASD undergoing their first ASD evaluation. Parent belief that their child had ASD was highest among parents of White children. White children whose parents believed the child had ASD had lower ASD severity. Parents of Black/African American and Hispanic children were more likely to report communication conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Cultural expectations of child behavior and stigma surrounding developmental disabilities may also contribute to delayed identification of autism in certain populations ( Fisher et al, 2023 ; Pham & Charles, 2023 ; Zuckerman et al, 2018 ). Studies of parent reports of autism symptoms have found Black parents to be less likely than White parents to report concerns about their children’s social skills or restricted and repetitive behaviors and interests ( Azad et al, 2022 ; Donohue et al, 2019 ), even after controlling for autism severity ( Donohue et al, 2019 ), and may place more emphasis on behavioral concerns ( Mandell et al, 2007 ). Persistent racial and ethnic disparities in the prevalence of autism with co-occurring ID point to the need for increased access to culturally appropriate autism diagnostic and treatment services ( Dababnah et al, 2018 ) and improved outreach to provide parents the resources to recognize symptoms of ASD ( Čolić et al, 2022 ; Fisher et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cultural expectations of child behavior and stigma surrounding developmental disabilities may also contribute to delayed identification of autism in certain populations ( Fisher et al, 2023 ; Pham & Charles, 2023 ; Zuckerman et al, 2018 ). Studies of parent reports of autism symptoms have found Black parents to be less likely than White parents to report concerns about their children’s social skills or restricted and repetitive behaviors and interests ( Azad et al, 2022 ; Donohue et al, 2019 ), even after controlling for autism severity ( Donohue et al, 2019 ), and may place more emphasis on behavioral concerns ( Mandell et al, 2007 ). Persistent racial and ethnic disparities in the prevalence of autism with co-occurring ID point to the need for increased access to culturally appropriate autism diagnostic and treatment services ( Dababnah et al, 2018 ) and improved outreach to provide parents the resources to recognize symptoms of ASD ( Čolić et al, 2022 ; Fisher et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research has shown that while Latinx mothers will report general developmental delays, they are less likely than White mothers to report autism-specific concerns (Angell et al, 2018). Other research demonstrated that White caregivers are more likely to believe their child had autism during the evaluation process when compared to Black or Latinx caregivers (Azad et al, 2022).…”
Section: Driving Factors For Treatment Disparitiesmentioning
confidence: 99%
“…Factors related to caregiver and provider awareness of early signs of autism (Azad et al, 2021; DeVilbiss & Lee, 2014), caregiver access to diagnostic and early intervention services (Stahmer et al, 2019)…”
Section: Figurementioning
confidence: 99%